PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN PERPAJAKAN, PELAYANAN FISKUS, SANKSI ADMINISTRASI PADA KEPATUHAN WAJIB PAJAK RESTORAN - Katini, Ni Kadek Okta Yasi; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
Tax compliance is a situation where the taxpayer meets all tax obligations and the exercise of the right of taxation. For that,  tax compliance is high it is necessary to note the factors that influence taxpayer compliance. The purpose of this study was to determine the effect of awareness of taxpayers, tax knowledge, service tax authorities, and administrative sanctions on taxpayer compliance restaurants in the Badung Regency. Samples are taken by 92 respondents consisting of Owner or Manager is based on probability sampling method with syistematic random sampling. Techniques of  data analysis is multiple linear regression analysis. Based on the analysis, the awareness of taxpayers, tax knowledge, service tax authorities and administrative sanctions have positive influence on taxpayer compliance restaurants in the Badung Regency.
Keywords: Taxpayer awareness, tax knowledge, service tax authorities, administrative sanctions, tax compliance, restaurants.